PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PERENCANAAN ANGGARAN, POLITIK PENGANGGARAN, DAN TRANSPARANSI PUBLIK TERHADAP SINKRONISASI DOKUMEN APBD DENGAN KUA-PPAS PADA PEMERINTAH KABUPATEN LOMBOK BARAT - Nurhidayati Hikmah; Busaini .; Sri Pancawati (Jurnal Akuntansi Aktual, 2015)
This study aims to determine the effect of human resources capacity, budget planning, politi-cal budgeting, and public transparency on the synchronization between Regional Revenues and expen-ditures budget (APBD) document and General Policy of Regional Revenues and Expenditures Budget(KUA) and Provisional Budget Ceiling Priority (PPAS) document. The population in this study wascouncilors and officer/staff involved in the preparation of the Work Plan Budget (RKA) SKPD includes33 SKPD. The sampling method using census method, where all the population became the samples asmuch as 127 people. The data in this study using primary data. The data obtained were analyzedthrough multiple linear regression tests. Hypotheses simultaneously and partially tested by F test and ttest. Results of this study showed that simultaneous variable capacity of human resources, budgetplanning, political budgeting, and public transparency has a positive and significant impact on thesynchronization between APBD documents and KUA-PPAS documents. And in partial, the capacity ofhuman resources, budget planning, political budgeting, and public transparency has a positive andsignificant impact on the synchronization between APBD documents and KUA-PPAS documents. Theimplications of this research, can be useful as a conceptual contribution to policy makers, especially inWest Lombok Regency Government and Parliament should be consistent and have a high commitment inbudgeting and KUA-PPAS.Keywords:budget, KUA-PPAS, human resources capacity, budget planning, budgeting politics andpublic transparency